Characterization and production of conductive filler from oil palm ash and its performance in epoxy matrix - Mamat, O. (Engg Journals Publications, 2016)
Oil Palm Ash (OPA) was investigated and the FESEM studies showed medium sized particle with a crushed structure. An XRD diffractogram of OPA showed that the obtained OPA contain aluminum, silicon and they exist in their oxide form as indicated by the high percentage of oxygen (36) with little traces of potassium oxide, calcium oxide, magnesium oxide. while FTIR analysis indicated the occurrence of functional groups such as OH groups, silanol hydroxyl groups of silica or the N-H stretching vibration free imines, aromatic C-H and C-Br alkyl functional group and the presence of methyl CH3. OPA was carbonized in a furnace with the control flow of nitrogen and ball milled at 100 rpm for 3 hours to obtain a carbonized particle with a diameter of 77.9- 140.9 nm. The synthesized carbon black (CB) Particle was dispersed in epoxy resin (DGEBA) at different loading to produce an electrically conductive polymer with a well-dispersed network of electrical conducting particles.